Magnetic resonance imaging of coeliac disease - Costigan, Carolyn (2020)
Background Coeliac disease is an autoimmune disease affecting primarily the small bowel mucosa. Diagnosis is by blood test and duodenal biopsy, with the patient on a gluten-containing diet. The only treatment currently available is a gluten free diet (GFD). Further work is required to understand macroscopic gastrointestinal (GI) function and mechanisms of symptoms in coeliac disease. Magnetic Resonance Imaging (MRI) offers a unique tool to study GI fluid volumes, organ volumes and gut transit non-invasively.